2020
DOI: 10.1002/cbdv.202000073
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Antioxidant Potential and Enzymes Inhibitory Properties of Globe Artichoke By‐Products

Abstract: In this study, chemical composition and in vitro biological activities of artichoke by‐products (leaves, floral stems and bracts) issued from two Tunisian varieties were evaluated. Analysis was performed by means of high‐performance liquid chromatography with diode array detection coupled to electrospray ionization mass spectrometric (LC/DAD/ESI‐MS). Total phenolic (TPC) and flavonoid (TFC) contents as well as the antioxidant activity conducted by three complementary methods, DPPH, ABTS and FRAP tests, were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 36 publications
2
9
1
Order By: Relevance
“…The resulting chromatograms, depicted in Figure 1 , showed that the two extracts presented similar chromatogram profiles and that PEF pre-treatment of artichoke stems remarkably increased the peak areas of the major phenolic compounds present in the AEs, corresponding to chlorogenic acid (peak 3), followed by naringin (peak 7), rutin (peak 8) catechin (peak 2), epicatechin (peak 4), sinapic acid (peak 6), phlorizin (peak 9), cynarine (peak 5) and gallic acid (peak 1). The obtained results are consistent with previous findings by other authors [ 18 , 23 ]. They reported that, among phenolic compounds, caffeoylquinic acids were the most abundant hydroxycinnamic acids in artichoke residues, with chlorogenic acid being present to a greater extent.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The resulting chromatograms, depicted in Figure 1 , showed that the two extracts presented similar chromatogram profiles and that PEF pre-treatment of artichoke stems remarkably increased the peak areas of the major phenolic compounds present in the AEs, corresponding to chlorogenic acid (peak 3), followed by naringin (peak 7), rutin (peak 8) catechin (peak 2), epicatechin (peak 4), sinapic acid (peak 6), phlorizin (peak 9), cynarine (peak 5) and gallic acid (peak 1). The obtained results are consistent with previous findings by other authors [ 18 , 23 ]. They reported that, among phenolic compounds, caffeoylquinic acids were the most abundant hydroxycinnamic acids in artichoke residues, with chlorogenic acid being present to a greater extent.…”
Section: Resultssupporting
confidence: 94%
“…For instance, the TPCs of extracts from artichoke sprouts and stalks from different Italian locations detected by Ferioli and D’Antuono were in the range of 8.9–34.9 mg GAE/gDW [ 50 ]. Similarly, Rejeb et al found the TPCs of extracts from artichoke floral stems to be equal to 10.689 ± 0.324 mg GAE/gDW [ 23 ]. Moreover, the composition, in terms of the most abundant phenolic compounds, of the extracts from untreated and PEF-treated artichoke stems subject to optimal processing conditions was assessed via HPLC–PDA analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, other reports of AChE inhibitory activity where the catechin content was high enough could be also explained [ 67 , 78 , 83 ]. Ben Rejeb et al (2020) stated that extracts from artichoke by-products (leaves, bracts and stems) inhibited AChE and BChE activity, and they related this to the presence of flavonoids in a positive and significant way [ 93 ]. In fact, they highlighted luteolin and its derivatives as the main contributing factor, and reported that flavonoids such as quercetin were able to block the entrance to the active site of AChE and BChE enzymes.…”
Section: Phenolic Compounds From Fruit and Vegetable By-products: Neu...mentioning
confidence: 99%
“… Main mechanisms through which plant extracts and their phenolic compounds exert their neuroprotective effects, as well as key cell processes involved. Finally, several references in which this information is demonstrated [ 30 , 34 , 41 , 48 , 57 , 58 , 75 , 79 , 80 , 81 , 85 , 86 , 87 , 88 , 89 , 92 , 93 , 95 , 102 , 108 , 110 , 115 , 123 , 130 , 131 ]. …”
Section: Figurementioning
confidence: 99%